Response surface methodology approach for optimisation of alkaline hydrolysis of Jatropha Curcas oil via microwave assisted - Yusuf, N.R. (Italian Association of Chemical Engineering - AIDIC, 2015)
The production of fatty acid by alkaline hydrolysis method from Jatropha Curcas oil using microwave assisted irradation system has been investigated. This fatty acid is widely used as raw materials for biochemicals industry. The optimisation of alkaline hydrolysis variables such as temperature, catalyst concentration loading, reaction time and oil to solvent ratio was carried out using central composite design (CCD) in response to surface methodology (RSM) to achieve maximum free fatty acid yield ( FFA). Analysis of variance (ANOVA) analysis shows that the catalyst concentration are the most significant variance effecting the yield of FFA, with R2 = 0.9827 indicating good fitting of the suggested model. The highest fatty acids yield was 98 achieved at the optimum condition of 95 Â°C, 1.75 M of ethanolic KOH concentration, 1:68 oil to solvent ratio and 15 min of reaction time in 3,000 W microwave power system. This study reports under optimised condition, fatty acids yield was significantly increased and this also showed the potential of Jatropha Curcas oil as feedstock for fatty acids production. Copyright Â© 2015, AIDIC Servizi S.r.l.,.